TUNTUTAN PEMEGANG HAK CIPTA ATAS PELANGGARAN HAK CIPTA LAGU/MUSIK MELALUI PLATFORM YOUTUBE - Valentino, Nova; Ratnawati, Elfrida (UNES Law Review, 2023)
In the elucidation of Law Number 28 of 2014 Concerning Copyright, it is one part of intellectual property that has the widest range of protected objects. Currently, people are enjoying or looking for entertainment, especially songs, simply through digital platforms. This article will discuss claims for compensation for copyright infringement through the YouTube digital platform. The method used in this study is normative law, while the data used includes both primary and secondary data. From the results of research through analysis of cases of copyright disputes between Nagaswara who is the copyright holder of the song "Lagi Syantik" and Gen Halilintar it was found that the use of the song works used by Gen Halilintar through the YouTube platform, it is not enough just to include the name of the creator. However, you must first obtain permission from the creator or copyright holder. The permit referred to can be in the form of a mechanical rights license or performing rights. If a song is used without permission, problems with criminal or civil threats will arise if the song is used without permission from the creator or copyright holder.